(untitled) (Research, Society and Development, 2022)
Objective: To assess whether the CAD/CAM technology is superior to the conventional technique for making Tissue Born total dentures. Methodology: This review followed the PRISMA recommendations. A systematic review was carried out by two calibrated reviewers in the Medline-PubMed, Scopus, Scielo, Lilacs, Web of Science and Cochrane Library databases, using the descriptors: “Complete denture”, “Complete dentures”, “Total denture”, “Total dentures”, “Complete prosthesis”, “Complete prosthesis”, “Total prosthesis”, “Total prosthesis”, “Computer Aided Design”, “Computer Aided Manufacturing”, “CAD/CAM”, ’’Benefits” and “Advantage”. Only in vitro studies comparing CAD/CAM technology (printing or milling) with conventional manufacturing were included, and studies without a control group and prostheses on implants were excluded. Results: The strategy used resulted in 410 articles. Of these, 11 met the inclusion criteria. After reading in full, only 6 were included in the systematic review. Despite requiring a high investment and professional training, the selected studies demonstrated the following advantages of the CAD/CAM system over the conventional one: less monomer release and better adaptation of the dentures Conclusion: The manufacturing process of total dentures through the system CAD/CAM proved to be advantageous compared to the conventional method, the main one being the lower release of monomer, accompanied by better biomechanical qualities and marginal adaptation, despite its high cost.